2016
DOI: 10.1073/pnas.1608950113
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced intensity of global tropical cyclones during the mid-Pliocene warm period

Abstract: Given the threats that tropical cyclones (TC) pose to people and infrastructure, there is significant interest in how the climatology of these storms may change with climate. The global historical record has been extensively examined, but it is short and plagued with recurring questions about its homogeneity, limiting its effectiveness at assessing how TCs vary with climate. Past warm intervals provide an opportunity to quantify TC behavior in a warmer-than-present world. Here, we use a TC-resolving (∼25 km) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 33 publications
5
32
0
Order By: Relevance
“…The two experiments are designed to (i) consider the uncertainty in the estimated mid-Piacenzian TC activity (Yan et al 2016) and (ii) isolate the role of mixing over the central-eastern North Pacific, which is thought to be one of the key regions linking the extratropical and tropical ocean (Gu and Philander 1997). The other boundary conditions (e.g., topography and land cover) in the sensitivity experiments are identical to those in MP.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The two experiments are designed to (i) consider the uncertainty in the estimated mid-Piacenzian TC activity (Yan et al 2016) and (ii) isolate the role of mixing over the central-eastern North Pacific, which is thought to be one of the key regions linking the extratropical and tropical ocean (Gu and Philander 1997). The other boundary conditions (e.g., topography and land cover) in the sensitivity experiments are identical to those in MP.…”
Section: Experimental Designmentioning
confidence: 99%
“…In addition to changes in the mean state, extreme events, such as tropical cyclones (TCs), also experienced remarkable variations in the mid-Piacenzian. Using an ultra-high resolution (~25 km) climate model, Yan et al (2016) suggested that global TCs tended to be stronger and more powerful in the mid-Piacenzian. Notably, TCs not only passively vary with climate, but also play an important role in the vertical mixing of the upper ocean and in driving oceanic poleward heat transport (Emanuel 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Boreal forests expanded northward to replace tundra, and the extent of arid deserts was reduced (Salzmann et al, ). Tropical cyclone became stronger and lasted longer, with a poleward shift of the location of peak intensity (Yan et al, ). These climatic features share similarities with the projected climate in a future greenhouse world (Christensen et al, ; Haywood et al, ).…”
Section: Introductionmentioning
confidence: 99%